Sporotrichosis in Renal Transplant Patients - Paulo Gewehr; Bruno Jung; Valerio Aquino; Roberto C Manfro; Fábio Spuldaro; Regis G Rosa; Luciano Z Goldani (Canadian Journal of Infectious Diseases and Medical Microbiology)
The current report describes two renal transplant recipients who presented with sporotrichosis. In addition, the authors review the general aspects of sporotrichosis in renal transplant recipients reported in the literature. Sporotrichosis is a rare fungal infection in transplant patients and has been reported primarily in renal transplant recipients not treated with antifungal prophylaxis. Extracutaneous forms of sporotrichosis without skin manifestations and no previous history of traumatic injuries have been described in such patients and are difficult to diagnose. Renal transplant recipients with sporotrichosis described in the present report were successfully treated with antifungal therapy including amphotericin B deoxycholate, lipid amphotericin B formulations, fluconazole and itraconazole.